PERAN SERTA LEMBAGA KERAPATAN ADAT NAGARI DALAM MEWUJUDKAN NAGARI MADANI DI KABUPATEN AGAM - Darmini Roza; Teddy Martha (LPPM Universitas Ekasakti Padang, 2022)
The implementation of the Nagari Madani in Agam Regency is regulated in the Regulation of the Regent of Agam Number 74 of 2016 concerning Guidelines for the Implementation of the Nagari Madani. This research is a legal research with analytical descriptive specifications. The Role of the Nagari Customary Density Institution in Realizing the Nagari Madani in Agam Regency is to participate directly in the Maghrib Koran activities, by giving recitations by the niniak mamak together with the nagari ulama at the end of each evening praying together at the surau. Collecting data on who is entitled to receive zakat for each of their people, and collecting zakat from all people. KAN conducts socialization and provides guidance to the community in every crime prevention activity in the nagari. Organize women and children protection groups by bundo kanduang in collaboration with the police. The obstacle encountered in the participation of the Nagari Customary Density Institution in Realizing the Nagari Madani in Agam Regency is the occurrence of disagreements between the parties. KAN's inability to enforce coercion so that the opinion given is carried out, is one of the obstacles that KAN encounters, especially the unavailability of devices capable of carrying out coercive measures against the results of the decision. In crime prevention activities, it is often found that KAN elements are arrogant so that they interfere with KAN's performance in the success of Nagari Madani activities. The existence of a conflict between the Wali Nagari and the Nagari Representative Council (DPN) and KAN is an inhibiting factor in the implementation of the Nagari Madani movement in Agam Regency.